Polyurethane foam as a soilless growing media: demonstrating the importance of physical property optimisation - Wright, Harry C.; Wilkinson, Samuel W.; Morgan, Caleb W.; Rolfe, Stephen A.; Cameron, Duncan D.; Ryan, Anthony J. (Frontiers in Horticulture, 2025)
IntroductionIncreasing adoption of hydroponics in food production has increased the demand for soilless growing media. Given the variety of crops and cultivation techniques used in soilless systems, optimising the physical properties of novel media for specific crops and systems presents an opportunity, as some growing media, such as mineral wool, provide only a limited set of physical properties. Polyurethane foams (PUFs), a promising soilless growing media, offer flexibility, as foams with a diverse range of physical properties can be produced.MethodsWe examined 10 distinct PUF formulations with a range of physical properties (cell size [d], open cell fraction [peff], maximum water uptake height [Hmax], water uptake rate [Wur]) through germination and growth trials. Additionally, investigations into whether these media influence disease susceptibility were conducted by inoculating tomato plants with Pythium spp. Results and discussionGermination trials using lettuce and tomato identified four PUF formulations as unsuitable. A small-scale growth trial demonstrated that the remaining formulations performed comparably to mineral wool (MW). Three of these formulations were tested in trials for lettuce and pak choi in a NFT system and for tomato using a dripper-fed system. Results indicated that two PUF formulations surpassed MW in vegetative growth in tomato trials (F04: d = 669 µm, peff = 0.694, Hmax = 2.94 cm, Wur = 0.023 cm s-1; F08: d = 624 µm, peff = 0.38, Hmax = 2.35 cm, Wur = 0.012 cm s-1) and two PUF formulations matched MW in lettuce yield in NFT trials (F04: properties detailed above; F07: d = 683 µm, peff = 0.897, Hmax = 3.07 cm, Wur = 0.055 cm s-1). Pak choi plants in foam displayed slightly lower yields than those in MW, although differences were not significant. All foam samples suppressed Pythium inoculation, as evidenced by no reduction in germination rates or seedling mass when compared to the uninoculated samples, warranting further investigation into disease suppression. These growth results suggest that growing media physical properties should be optimised according to both hydroponic technique and crop to maximise yields and that PUF media can aid in developing tailored growing media for specific crop and systems.